5x - 8a + 4a - 2x + a
Here, all you have to do is combine like terms:
5x - 8a + 4a - 2x + a ===> 5x - 2x - 8a + 4a + a ===> 3x - 3a
Thus, your answer is: 3x - 3a OR 3(x - a)
5x - 8a + 4a - 2x + a
Here, all you have to do is combine like terms:
5x - 8a + 4a - 2x + a ===> 5x - 2x - 8a + 4a + a ===> 3x - 3a
Thus, your answer is: 3x - 3a OR 3(x - a)
5x-8a+4a-2x+a
I start by underlining the corresponding letters, then combining.
-8a+4a=-4a
-4a+a=-3a Done with A's
Now 5x-2x=3x done with x's so that leaves you with 3x-3a
So